2020
DOI: 10.1002/etc.4713
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activity and Lipid Peroxidation in Aporrectodea caliginosa Earthworms Exposed to Silver Nanoparticles and Silver Nitrate in Spiked Soil

Abstract: Silver nanoparticles (AgNPs) from industrial use, discharged via the land application of sewage sludge, are interacting with soil biota, including earthworms. In affected organisms, excessive production of reactive oxygen species can result in lipid peroxidation, shifting the balance between oxidants and antioxidants to cause oxidative stress. We determined selected lower‐tier biomarkers such as antioxidant responses and lipid peroxidation in Aporrectodea caliginosa earthworms exposed to soils spiked with AgNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Exposure to AgNPs may cause lipid peroxidation in certain cell lines or organisms [30][31][32]. Multiple studies indicate various cancers with an EMT phenotype are vulnerable to agents that induce lipid peroxidation [14,15], but differences in the sensitivity of CLBC and BLBC cells to lipid peroxidation have not been assessed.…”
Section: Agnps Induce Lipid Peroxidation and 4-hne-histidine Adduct Formation In Clbc But Not In Blbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to AgNPs may cause lipid peroxidation in certain cell lines or organisms [30][31][32]. Multiple studies indicate various cancers with an EMT phenotype are vulnerable to agents that induce lipid peroxidation [14,15], but differences in the sensitivity of CLBC and BLBC cells to lipid peroxidation have not been assessed.…”
Section: Agnps Induce Lipid Peroxidation and 4-hne-histidine Adduct Formation In Clbc But Not In Blbcmentioning
confidence: 99%
“…We and others found that certain breast cancer cell lines are more sensitive to silver nanoparticle (AgNP) exposure than non-malignant mammary epithelial cells [23][24][25][26]. Notably, AgNP exposure increases protein oxidation and proteotoxic stress [23][24][25][27][28][29] and may cause lipid peroxidation in certain cells and organisms [30][31][32]. However, there is considerable heterogeneity in the relative sensitivity of various cancers to AgNP exposure [23][24][25]27,29,33,34], and it is not known if cancers with an EMT phenotype are more susceptible than other cancers or normal cells to proteotoxic stress or lipid peroxidation caused by exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of ASBO, there is an increase in intra-abdominal pressure, which leads to the development of ischemic-reperfusion syndrome; there is an increase in reactive oxygen species and damage to cell membranes, which ultimately leads to necrosis. Activation of lipid peroxidation processes leads to an imbalance in the APS, which exacerbates the development of endogenous intoxication and enteral insufficiency syndromes [ 6 7 ]. Increasing the production of free radicals reduces the protective properties of the intestinal mucosa and facilitates bacterial translocation, naturally increasing the risk of failure of intestinal anastomoses.…”
Section: Disscusionmentioning
confidence: 99%
“…According to some studies, surgery increases the intensity of LPO, which promotes the entry into the bloodstream of unoxidized breakdown products [ 11 ]. However, the status and activity of APS blood do not always objectively reflect changes in organs and systems.…”
Section: Disscusionmentioning
confidence: 99%
“…In the course of in vivo earthworm studies assessing different endpoints (e.g., survival, reproduction, bioaccumulation, apoptosis, and mortality) AgNPs exerted harmful effects at the individual level. The majority of the current studies ( Table 1 ) have applied Eisenia fetida ( Oligochaeta , Lumbricidae ) as a model organism [ 35 , 36 ] to monitor the AgNPs’ deleterious consequences; however, several studies also exist that applied other earthworm species [ 14 , 17 , 23 , 29 , 30 , 31 , 32 , 33 , 37 , 38 ]. The same amount of coated AgNPs (with either polyvinylpyrrolidone (PVP) or oleic acids) or ionic silver caused no remarkable impacts on mortality and growth in E. fetida exposed in soil.…”
Section: Risk Assessment Of Silver Nanoparticles To Soil Invertebrmentioning
confidence: 99%